Study of Mathematics Self Efficacy Ability Students in Critical Thinking Ability - Italyani Nurhaifa; Turmudi (International Conference on Elementary Education, 2023)
Self-efficacy will help students encourage themselves to feel able to complete tasks from simple to complex problems and maximize their creativity until the problem is resolved. This article aims to examine students' mathematical self-efficacy abilities in critical thinking. The method used is qualitative by collecting library data. Self-efficacy plays an important role in everything, especially for students who find it difficult to solve mathematical problems through critical thinking activities. With high self-efficacy, students are expected to be able to successfully solve mathematical problems and be able to think critically. Students with high selfefficacy believe that they can do well on math tests, understand the most difficult material, perform tasks with the best effort in math, and are able to master competencies in math class, and tend to have superior math achievements. On the other hand, students with low mathematical self-efficacy tend to be vulnerable and give up easily in solving math problems and students' failure to solve math problems is assumed to be due to their lack of mathematical abilities.